Catalyst, silicon-tin composite material, carbon-coated material of silicon-tin composite material, preparation method, application and battery
By using oxidation and reduction treatment of tin nanoparticle catalyst and carbon-based materials, silicon nanowires are grown, solving the problem of low capacity and first-term effectiveness of existing silicon-carbon composite materials in lithium-ion battery applications, and achieving efficient and low-cost silicon-tin composite materials preparation and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411999175.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
In the application of lithium-ion battery, existing silicon-carbon composite materials have problems such as low capacity, low first-term efficiency and unsuitable production processes for large-scale preparation.
A catalyst containing tin nanoparticles is used to oxidize and reduce the mixture with a carbon-based material or ITO-based material as a support to form tin nanoparticles attached to the catalyst support, thereby growing silicon nanowires under heating conditions, and preparing a silicon-tin composite material with excellent cycle stability and rate performance.
It realizes high cycle stability and rate performance of the negative electrode material of lithium-ion battery, reduces production costs and energy consumption, and is suitable for large-scale preparation.
Smart Images

Figure CN119793436A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst, a silicon-tin composite material and a carbon-coated material thereof, a preparation method, an application and a battery. Background Art
[0002] Silicon has a moderate operating voltage (~0.4V vs Li / Li + ), high theoretical specific capacity (Li 22 Si5, 4200mAh g -1 ), environmentally friendly and abundant in the earth, and can be used as the negative electrode graphite of commercial lithium-ion batteries (LIBs) (theoretical specific capacity 372 mAh g -1 ) and can be used in the electric vehicle industry in the future. However, the following problems of silicon hinder its commercial application.
[0003] First, silicon undergoes a huge volume change (>300%) during cycling, which leads to the rupture and pulverization of the silicon anode, separation from the current collector and the formation of an unstable solid electrolyte interface (SEI) film. Second, silicon has a poor intrinsic conductivity (10 -5 ~10 - 3 S cm -1 ) and its slow lithium ion diffusion kinetics (10 -14 ~10 -13 cm 2 s -1 ); Finally, the raw material cost of silicon is high, the process is complicated and the reaction conditions are harsh. Therefore, in order to obtain a higher performance silicon negative electrode while meeting the requirements of commercial applications, the above silicon problems must be solved.
[0004] Patent application CN201611140651.6 discloses a method for preparing a multi-wire array of Si nanowires using tin dioxide, and the preparation method is as follows: a fluorine-doped tin oxide coating is coated on the surface of a conductive glass, and heated in a plasma enhanced chemical vapor deposition device, and then a multi-wire array of silicon nanowires is formed under the conditions of introducing silane and hydrogen. The obtained nanowires have a high yield and a certain degree of energy consumption reduction, but the quality of the silicon nanowires is affected. The tin dioxide is not removed, and the presence of a large amount of oxygen is prone to cause irreversible capacity loss. In addition, when applied to the negative electrode of a lithium-ion battery, the silicon nanowires are in direct contact with the electrolyte, and it is difficult to form a stable SEI film, so the electrochemical performance is poor.
[0005] Patent application CN202280044797.8 discloses a method for preparing a material containing silicon nanowires and tin, wherein the preparation method is: using stannous chloride as a catalyst precursor to grow silicon nanowires on the surface of graphite / silicon particles through solid-solid mixing and medium temperature. The obtained lithium-ion battery silicon-carbon composite material can control the electrochemical performance by adjusting the growth ratio of silicon nanowires, and the carbon layer after carbonization of organic matter on the surface of the nanowires contributes to the cyclic stability of the material. However, the production steps of this method are cumbersome, and the thickness and uniformity of the carbon layer cannot be controlled. Summary of the invention
[0006] The present invention provides a catalyst, a silicon-tin composite material and its carbon-coated material, a preparation method, an application and a battery to solve the defects of low capacity and low initial efficiency of batteries prepared by existing silicon-carbon composite materials and the production process is not suitable for large-scale preparation. The method has low cost, simple process and can be produced continuously. The obtained material is applied to the negative electrode of lithium-ion batteries and has excellent cycle stability and rate performance.
[0007] The present invention adopts the following technical solutions to solve the above technical problems:
[0008] The invention provides a catalyst, which comprises tin nanoparticles; the particle size of the tin nanoparticles is 20-120nm; the catalyst is attached to the surface of a catalyst carrier; the particle size of the catalyst carrier is 1-100μm; the catalyst carrier is a carbon-based material, an ITO-based material or a carbonaceous polymer.
[0009] In the present invention, the average particle size of the tin nanoparticles may be 46 nm or 70 nm.
[0010] In the present invention, the particle size of the catalyst carrier may be 4-28 μm.
[0011] In a specific embodiment, the D50 of the catalyst support may be 8-15 μm, for example 12.3 μm;
[0012] In a preferred embodiment, the catalyst carrier is a carbon-based material and / or a carbonaceous polymer, such as graphite; more preferably, the graphite is one or more of natural graphite, artificial graphite and expanded graphite; wherein the D 50 Preferably, it is 8-15 μm, for example, 12.3 μm.
[0013] Preferably, when the catalyst carrier is a carbon substrate, the size of the carbon substrate is 4-28 μm, for example, 12.3 nm; the BET area can be 1-150 m 2 / g, for example 1.524m 2 / g.
[0014] Preferably, the mass ratio of catalyst to catalyst carrier is (0.05-0.3):1.
[0015] The present invention provides a method for preparing a catalyst, which comprises the following steps:
[0016] A mixture of a catalyst carrier, stannous chloride dihydrate and a solvent is oxidized and reduced to obtain tin nanoparticles attached to the catalyst carrier; the oxidation temperature is 180-500°C; the oxidation time is 1-2h; the reduction temperature is 500-900°C; the reduction time is 2-4h; the particle size of the catalyst carrier is 1-100μm; the catalyst carrier is selected from at least one of a carbon-based material, an ITO-based material and a carbonaceous polymer.
[0017] In the present invention, the solvent is a conventional solvent in the art, and can be one or more of methanol, ethanol, isopropanol and deionized water, for example, a mixture of deionized water and ethanol in a volume ratio of 7:3.
[0018] In the present invention, the mass ratio of the catalyst carrier, the catalyst and the solvent may be 1:(0.05-0.3):(2-5), for example 1:0.06:2.5 or 1:0.2:2.5.
[0019] In the present invention, preferably, the particle size of the catalyst carrier is 4-28 μm.
[0020] In a specific embodiment, the D50 of the catalyst support may be 8-15 μm, for example 12.3 μm.
[0021] In the present invention, the catalyst carrier may be a carbon-based material and / or a carbonaceous polymer, such as graphite. The graphite is conventionally used in the art, preferably one or more of natural graphite, artificial graphite and expanded graphite. 50 The size of the catalyst support may be 8-15 μm, for example, 12.3 μm. When the catalyst support is a carbon substrate, the size of the carbon substrate may be 4-28 μm, and the BET area may be 1-150 m 2 / g.
[0022] In a preferred embodiment, the mixture is obtained by wet mixing. The wet mixing preferably comprises the following steps: first dissolving the stannous chloride dihydrate, and then adding the catalyst carrier.
[0023] The catalyst dissolution process preferably further comprises stirring or ultrasonic dispersion. The stirring temperature may be room temperature. The room temperature may be 25-40° C., such as 30° C. The stirring time may be 10-40 min, such as 10 min or 20 min.
[0024] In a preferred embodiment, the catalyst support is added under stirring conditions, wherein the stirring temperature may be 60 to 90° C., such as 80° C., and wherein the stirring time may be 3 to 6 hours, such as 2 hours.
[0025] In a preferred embodiment, before the oxidation, the process further includes: removing the solvent and then drying. The drying is a conventional drying method in the art; the drying time can be 6-24 hours, for example, 12 hours. The drying temperature can be 90-200°C, for example, 120°C.
[0026] Wherein, the method for removing the solvent is a conventional method in the art, and the method may be a spray drying method, an impregnation method, a sol-gel method or a coprecipitation method, preferably a spray drying method. The feed temperature of the spray drying method may be 120-180°C, for example, 150°C. The discharge temperature of the spray drying method may be 60-100°C, for example, 80°C. The feed rate of the spray drying method may be 20-80mL / min, for example, 20mL / min.
[0027] Compared with the spray drying method, the impregnation method, sol-gel method and co-precipitation method require precise settings of parameters such as the type of precipitant, solution concentration, and temperature. The repeatability is poor, and there may be certain differences in product quality between different batches, resulting in uneven diameter and distribution of the catalyst, making it difficult to control the growth size of silicon nanowires.
[0028] The catalyst particles obtained by spray drying are more uniform in size and suitable for large-scale preparation. The parameters are easy to control and have good repeatability, which can ensure the quality stability of different batches of products. By adjusting the spray parameters, such as the type of atomizer, spray pressure, droplet size, etc., the size of the catalyst particles can be effectively controlled. Smaller droplets form smaller catalyst particles during the drying process, and the distribution range of the particle size is relatively narrow. Small-sized catalyst particles are conducive to the nucleation and growth of silicon nanowires in the gas-liquid-solid growth mechanism, and can grow nanowires with smaller diameters and longer lengths.
[0029] In the present invention, the oxidation is an oxidation treatment conventionally used in the art, for example, carried out in a tube furnace.
[0030] The preparation method of the present invention can achieve different diameters of tin nanoparticles obtained by oxidation treatment at different temperatures, and further can adjust the thickness of subsequent silicon nanowires by controlling the diameter of the tin nanoparticles.
[0031] In the present invention, the oxidizing atmosphere is an atmosphere conventionally used in the art, such as air or oxygen.
[0032] In the present invention, the oxidation temperature may be 220-450°C, such as 350°C or 450°C.
[0033] In the present invention, the oxidation time can be 1 h or 2 h.
[0034] In the present invention, the heating rate of the oxidation may be 5-15°C / min, for example, 10°C / min.
[0035] In the present invention, the reduction is a reduction process conventionally used in the art, for example, the reduction can be carried out in a tube furnace.
[0036] In a specific embodiment, the reduction is performed using a reducing gas. The reducing gas is a reducing gas conventionally used in the art, such as H2 or CO.
[0037] In the present invention, the flow rate of the reducing gas used in the reduction may be 2-6 L / min, for example 4 L / min.
[0038] In a preferred embodiment, the reducing gas is usually mixed with a non-reactive gas. The non-reactive gas is a gas conventionally used in the art, such as nitrogen or argon. The volume ratio of the reducing gas to the non-reactive gas is (1-10):(90-98), for example, 5:95.
[0039] In the present invention, the reduction temperature may be 600-800°C, such as 600°C or 700°C.
[0040] In the present invention, the reduction time may be 2 hours.
[0041] In the present invention, the temperature rise rate of the reduction may be 2-10° C. / min, for example 5° C. / min.
[0042] The present invention provides a catalyst prepared by adopting the catalyst preparation method.
[0043] The invention provides a silicon-tin composite material, which comprises a catalyst carrier, a catalyst and silicon nanowires growing outward with tin nanoparticles as anchor points; the catalyst is the catalyst described above; the catalyst carrier is the catalyst carrier described above; the content of the silicon nanowires is 24-80%, and the percentage is the mass percentage of silicon in the total amount of silicon and tin; the diameter of the silicon nanowires is 20-100nm, and the length of the silicon nanowires is 0.1-10μm; the tin content of the silicon-tin composite material is 20-76%, and the percentage is the mass percentage of tin in the total amount of silicon and tin.
[0044] The tin content is the mass percentage obtained by: tin / (silicon+tin)*100%.
[0045] The silicon content is the mass percentage obtained by: silicon / (silicon+tin)*100%.
[0046] The content of the silicon nanowires is calculated as follows: silicon / (silicon+tin)*100%.
[0047] The diameter of the silicon nanowire may be 35 nm or 57 nm.
[0048] The length of the silicon nanowire may be 5.2 μm or 2.5 μm.
[0049] The content of the silicon nanowires may be 73% or 58%.
[0050] The silicon content of the silicon-tin composite material may be 73% or 58%.
[0051] The tin content of the silicon-tin composite material may be 27% or 42%.
[0052] The invention provides a method for preparing a silicon-tin composite material, which comprises the following steps: mixing the above-mentioned catalyst with a silicon source under heating conditions; the heating temperature is 400-700°C.
[0053] In the present invention, after the above heating step, silicon nanowires are grown on the surface of the catalyst carrier with the catalyst as an anchor point.
[0054] In a preferred embodiment, silicon nanowires are grown using a silicon deposition method.
[0055] In the present invention, the silicon source is a silicon source conventionally used in the art. The silicon source may be silane, such as one or more of disilane, chlorosilane, dichlorosilane, trichlorosilane, phenylsilane, diphenylsilane and trisilane.
[0056] In the present invention, the heating may be a heating method conventionally used in the art, such as being performed in a tube furnace.
[0057] In the present invention, the heating rate may be 2-10°C / min, for example 5°C / min.
[0058] In the present invention, the heating temperature may be 450-550°C, for example 450°C or 550°C.
[0059] In the present invention, the heating time may be 30 to 200 minutes, for example, 60 minutes.
[0060] In the present invention, the flow rate of the silicon source may be 2-6 L / min, for example, 5 L / min.
[0061] The present invention also provides a silicon-tin composite material prepared by the method for preparing the silicon-tin composite material.
[0062] The present invention also provides a carbon-coated silicon-tin composite material, which comprises a silicon-tin composite material and a carbon coating layer on the outside of a silicon nanowire; the silicon-tin composite material is the silicon-tin composite material as described above; the particle size of the carbon-coated silicon-tin composite material is 1-50 μm; the silicon content of the carbon-coated silicon-tin composite material is 0.96-70%, the percentage being the mass percentage of silicon in the total amount of silicon, tin and carbon; the tin content of the carbon-coated silicon-tin composite material is 0.96-30%, the percentage being the mass percentage of tin in the total amount of silicon, tin and carbon; and the thickness of the carbon coating layer is 10-100 nm.
[0063] The tin content of the carbon-coated silicon-tin composite material may be 2.70% or 8.06%.
[0064] The silicon content of the carbon-coated silicon-tin composite material may be 7.21% or 11.29%.
[0065] The carbon content of the carbon-coated silicon-tin composite material may be 1-95%, for example, 90.09% or 80.65%.
[0066] The thickness of the carbon coating layer of the carbon-coated silicon-tin composite material may be 55 nm or 12 nm.
[0067] The present invention also provides a method for preparing a carbon-coated silicon-tin composite material, which comprises the following steps: heating a mixture of the silicon-tin composite material and a carbon source;
[0068] In the present invention, the heating is a carbon coating method conventionally used in the art, for example, carried out in a tube furnace.
[0069] In the present invention, the carbon source is a carbon source conventionally used in the art, such as one or more of ethanol, benzene, methane, propane and acetylene, such as acetylene, which is usually coated in a mixed atmosphere with an inert atmosphere, such as a nitrogen atmosphere.
[0070] The heating temperature may be 500-800°C, preferably 600-700°C, for example 600°C.
[0071] The heating time may be 0.3-3 h, for example 1 h.
[0072] In the present invention, the heating rate during the coating treatment may be 2-10°C / min, for example 5°C / min.
[0073] In the present invention, the flow rate of the carbon source may be 2-6 L / min, for example 4 L / min.
[0074] In a preferred embodiment, steps S1-S3 can be performed continuously in the same equipment without frequent feeding / discharging.
[0075] The present invention provides an application of the silicon-tin composite material or the carbon-coated silicon-tin composite material for a negative electrode of a lithium ion battery.
[0076] The present invention provides a battery, which adopts the silicon-tin composite material or the carbon-coated silicon-tin composite material.
[0077] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0078] The reagents and raw materials used in the present invention are commercially available.
[0079] The positive and progressive effects of the present invention are:
[0080] (1) The catalyst of the present invention uses stannous chloride dihydrate as a catalyst precursor, and the obtained catalyst has good performance, can grow silicon nanowires at a lower temperature, and reduces energy consumption in the production process. The continuous preparation process improves production efficiency, reduces production costs, and is suitable for large-scale preparation.
[0081] (2) The preparation method of the catalyst of the present invention can adjust the diameter of the catalyst, which is convenient for regulating the loading amount of the nanowires, thereby making the size and distribution of the obtained silicon nanowires uniform.
[0082] (3) The silicon nanowires in the silicon-tin composite material of the present invention have a high aspect ratio and the tin particles contained therein have excellent electrical conductivity, which is helpful for electron transport. The silicon-tin composite material can be used to prepare a carbon-coated silicon-tin composite material with excellent electrochemical properties.
[0083] (4) The carbon-coated silicon-tin composite material of the present invention has a uniform carbon layer coated on the surface of silicon nanowires, which can improve the conductivity of silicon and inhibit the volume expansion of silicon during the cycle. It also prevents direct contact between silicon and electrolyte to form an unstable SEI film and avoids the deterioration of electrode performance. When used as a negative electrode material for batteries, it can relieve stress and strain and promote the diffusion of lithium ions. The network formed by the interconnection provides additional expansion space and creates a favorable ion and electron transmission path. The first discharge capacity of the carbon-coated silicon-tin composite material of the present invention is 598mAh g -1 The above, the first efficiency is more than 85% and the capacity retention rate is still above 76% after 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0084] Figure 1 Schematic diagram of the preparation method of the carbon-coated silicon-tin composite material obtained in Example 1.
[0085] Figure 2 This is a data graph of the charge and discharge specific capacity of the carbon-coated silicon-tin composite material obtained in Example 1.
[0086] Figure 3 This is the SEM image of the catalyst obtained in Example 1. DETAILED DESCRIPTION
[0087] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0088] Artificial graphite particles, C58-24050027 (FJ), were purchased from Shanghai Shanshan New Materials Co., Ltd.
[0089] Silicon wafer, ASC4-23040022, was purchased from Shanghai Shanshan New Materials Co., Ltd.
[0090] Example 1
[0091] Preparation of catalyst:
[0092] Mixing: 6 g of stannous chloride dihydrate was dissolved in 250 mL of a mixture of deionized water and ethanol (v:v = 7:3), stirred at 30 °C for 10 min, and then 100 g of artificial graphite particles (particle size 4-28 μm, BET area 1.524 m 2 / g, D50 is 12.3μm) was added to the mixed solution, and stirring was continued at 30°C for 2h. Finally, the mixture was placed in a spray dryer and dried for 12h, with a drying temperature of 120°C, a feed inlet temperature of 150°C, a discharge port temperature of 80°C, and a feed rate of 20mL / min;
[0093] Oxidation: Place the mixture obtained in the previous step in a reaction chamber and thermally oxidize it at 350°C for 1 h in oxygen to obtain graphite / tin oxide. The heating rate of thermal oxidation is 10°C / min.
[0094] Reduction: Stop the oxygen supply and purge the chamber with nitrogen for 5 min at a nitrogen flow rate of 4 L / min. Raise the reaction temperature to 600 °C at a heating rate of 5 °C / min. Then introduce a mixed atmosphere of hydrogen / argon (v:v = 5% / 95%) at a total flow rate of 4 L / min and react for 3 h. The SEM image of the obtained catalyst is shown in Figure 3 shown.
[0095] Preparation of silicon-tin composite materials:
[0096] Silicon deposition: Stop the introduction of hydrogen / argon mixed atmosphere and switch to nitrogen purge for 5 min at a flow rate of 4 L / min. When the temperature drops to 550°C, introduce monosilane gas at a silane flow rate of 5 L / min and react for 1 h.
[0097] Preparation of carbon-coated silicon-tin composite materials:
[0098] Carbon coating: Stop the introduction of silane and switch to nitrogen purge for 5 minutes, the nitrogen flow rate is 4L / min, then introduce acetylene, the acetylene flow rate is 4L / min, and the reaction temperature is raised to 600℃ at a heating rate of 5℃ / min, and the reaction is carried out for 1h to obtain a carbon-coated silicon-tin composite material. The relevant process diagram is as follows Figure 1 shown.
[0099] Example 2
[0100] Preparation of catalyst:
[0101] Mixing: Dissolve 20 g of stannous chloride dihydrate in a mixture of 250 mL of deionized water and ethanol (v:v = 7:3), then stir at 30 °C for 10 min. 2 / g, D50 is 12.3μm) was added to the mixed solution and stirred for 2h. Finally, the mixture was placed in a spray dryer and dried for 12h, with a drying temperature of 120°C, a feed inlet temperature of 150°C, a discharge port temperature of 80°C, and a feed rate of 20mL / min;
[0102] Oxidation: Place the mixture obtained in the previous step in a reaction chamber and thermally oxidize it at 450°C for 1 h in oxygen to obtain graphite / tin oxide. The heating rate of thermal oxidation is 10°C / min.
[0103] Reduction: stop introducing oxygen, use nitrogen to purge the chamber for 5 minutes, the nitrogen flow rate is 4L / min, and the reaction temperature is raised to 700°C at a heating rate of 5°C / min. Then, a mixed atmosphere of hydrogen / argon (v:v=5% / 95%) is introduced with a total flow rate of 4L / min, and the reaction is carried out for 2 hours.
[0104] Preparation of silicon-tin composite materials:
[0105] Silicon deposition: Stop the introduction of hydrogen / argon mixed atmosphere and switch to nitrogen purge for 5 min at a flow rate of 4 L / min. When the temperature drops to 450°C, introduce monosilane gas at a silane flow rate of 5 L / min and react for 1 h.
[0106] Preparation of carbon-coated silicon-tin composite materials:
[0107] Carbon coating: stop introducing silane and switch to nitrogen purging for 5 min at a nitrogen flow rate of 4 L / min, then introduce acetylene at a flow rate of 4 L / min, and raise the reaction temperature to 600 °C at a heating rate of 5 °C / min. React for 1 h to obtain a graphite / carbon-coated silicon nanowire composite material.
[0108] Comparative Example 1
[0109] The difference between this embodiment and embodiment 1 is that the carbon substrate is replaced with a silicon wafer, and after stirring and mixing, the mixture is directly dried in a vacuum oven at 90° C. The other conditions are exactly the same as those in embodiment 1.
[0110] Comparative Example 2
[0111] The difference between this comparative example and Example 1 is that the oxidation temperature during catalyst preparation is 550° C., and the other conditions are exactly the same as those in Example 1.
[0112] Comparative Example 3
[0113] The difference between this comparative example and Example 1 is that the reduction temperature during catalyst preparation is 450° C., and the other conditions are exactly the same as those in Example 1.
[0114] Comparative Example 4
[0115] The difference between this comparative example and Example 1 is that the temperature for growing the silicon nanowires is 750° C., and the other conditions are exactly the same as those in Example 1.
[0116] Comparative Example 5
[0117] The difference between this comparative example and Example 1 is that the oxidation time is 0.5 h, and the other conditions are exactly the same as those in Example 1.
[0118] Comparative Example 6
[0119] The difference between this comparative example and Example 1 is that the reduction time is 1 hour, and the other conditions are exactly the same as those in Example 1.
[0120] Comparative Example 7
[0121] The difference between this comparative example and Example 1 is that the catalyst is replaced with tin dioxide (mass is 4 g), and the other conditions are exactly the same as those in Example 1.
[0122] Comparative Example 8
[0123] The difference between this comparative example and Example 1 is that the catalyst is replaced with anhydrous stannous chloride (mass: 5 g), and the other conditions are exactly the same as those in Example 1.
[0124] Effect Example
[0125] 1. Element content determination method
[0126] Select an inductively coupled plasma optical emission spectrometer (ICP-OES), weigh 5g of sample, digest it with a mixture of nitric acid, hydrochloric acid and hydrofluoric acid (volume ratio of 3:1:1) in a microwave digestion instrument, keep it at 180℃ for 30 minutes, and adjust the volume to 80mL; prepare a series of standard solutions, measure the emission spectrum intensity or mass spectrum signal intensity to draw a standard curve. Introduce the solution to be tested into the instrument, calculate the silicon and tin content according to the standard curve, and indirectly calculate the carbon content.
[0127] 2. Method for determination of diameter or equivalent diameter of tin and silicon nanowires
[0128] Using a high-resolution transmission electron microscope, the sample (1 g) was ultrasonically dispersed in ethanol or acetone, dropped on a copper mesh or silicon wafer and air-dried or vacuum-dried. The dispersed tin particles / silicon nanowires were found using a high-magnification TEM, and the diameters or equivalent diameters of multiple tin particles / silicon nanowires were measured and the average value was calculated.
[0129] 3. Method for measuring the length of silicon nanowires / carbon coating thickness
[0130] Use TEM at high magnification to find silicon nanowires, measure the lengths or equivalent lengths and surface carbon coating thicknesses of multiple silicon nanowires, and calculate the average value.
[0131] 4. Electrochemical performance test method
[0132] At room temperature, the silicon-tin composite materials obtained in Examples 1-2 and Comparative Examples 1-8 were subjected to battery testing. The testing method was as follows: the active material, carboxymethyl cellulose (CMC) and conductive carbon black were mixed uniformly in a mass ratio of 8:1:1, and an appropriate amount of water was added to stir the mixture into a uniform slurry, which was then coated on a copper foil. After vacuum drying in a vacuum drying oven at 80°C for 6 hours, the mixture was rolled on a roller press and cut into 16 mm pole pieces. A lithium sheet was then used as the counter electrode, and 1.0 mol L -1 Lithium hexafluorophosphate was dissolved in a mixed solution containing ethylene carbonate and diethyl carbonate (volume ratio of 1:1) as the electrolyte. The above materials were assembled into a battery in a glove box. The capacity test was conducted on an American Arbin BT2000 battery tester, with a charge and discharge voltage range of 0.01 to 1.5V.
[0133] According to the above test method, Examples 1-2 and Comparative Examples 1-8 were tested, and the test results are shown in Table 1. The charge and discharge specific capacity data of the carbon-coated silicon-tin composite material obtained in Example 1 are as follows: Figure 2 shown.
[0134] Table 1
[0135]
[0136] Among them, the carbon content (%), silicon content (%), and tin content (%) in Table 1 are the mass percentages of these three substances in the total amount of carbon, silicon and tin respectively; the silicon nanowire content (%) is the mass percentage of silicon in the total amount of silicon and tin.
[0137] It can be seen from Examples 1-2 that the equivalent diameters of the tin nanoparticles in the catalysts prepared under different conditions have a certain range and are relatively stable. For example, the equivalent diameters of the tin nanoparticles in Examples 1-2 are between 46 and 70 nm, while the equivalent diameters of the tin nanoparticles in Comparative Examples 1-8 fluctuate greatly (between 24 and 150 nm), and the effects of different conditions on their sizes are regular, indicating that the method of the present invention can better control the size of tin nanoparticles; at the same time, the relative stability of the data shows that under the preparation method of the present invention, the diameter of the silicon nanowires has a certain uniformity.
[0138] The equivalent diameter of the silicon nanowires obtained in Examples 1-2 is between 60-70 nm. This thinner diameter helps to shorten the diffusion path of lithium ions and increase the diffusion rate of lithium ions, thereby improving the rate performance of the battery when it is used as a negative electrode material. At the same time, the high aspect ratio of the silicon nanowires enables them to form an interconnected network structure in the battery, providing additional expansion space for silicon when the volume changes, relieving stress and strain, reducing the possibility of silicon nanowire breakage and pulverization, and helping to maintain the integrity of the electrode structure, thereby improving cycle stability.
[0139] Compared with Examples 1-2, the electrochemical performance of Comparative Example 1 is poor. This is because the conductivity of the silicon wafer is relatively poor, and the transmission efficiency of electrons between the silicon wafer and the silicon nanowires is low, resulting in an increase in the internal resistance of the battery. During the charge and discharge process, due to the obstruction of electron transmission, a large energy loss will occur. During the battery cycle, the volume change of the silicon nanowires is more likely to cause separation from the silicon wafer substrate or structural damage, thereby affecting the cycle stability of the battery, causing the battery capacity to decay rapidly after multiple cycles.
[0140] Compared with Examples 1-2, the electrochemical performance of Comparative Example 2 is poor because the oxidation temperature is increased to 550°C in Comparative Example 2. Higher temperatures may cause the oxidation reaction to be too violent, making the growth rate of the tin oxide particles too fast and difficult to control. This may cause the agglomeration of the tin oxide particles to intensify. In the subsequent reduction process, the agglomerated tin oxide particles are difficult to be completely reduced to uniformly dispersed tin nanoparticles, resulting in uneven distribution of tin nanoparticles on the graphite substrate. In the silicon deposition stage, the unevenly distributed tin nanoparticles act as catalytic sites, which will cause the growth of silicon nanowires to become uneven. Some areas may grow thicker and denser silicon nanowires due to too many catalytic sites, while other areas may grow sparsely or not at all due to insufficient catalytic sites. This uneven silicon nanowire structure will cause many problems in lithium-ion battery applications. When the battery is charged and discharged, the uneven silicon nanowires will cause different rates of lithium ion insertion and extraction in different regions, resulting in large local stress, which is easy to cause the breakage and pulverization of silicon nanowires. At the same time, the uneven structure will also affect the transmission path of electrons, increase the internal resistance of the battery, and reduce the overall performance of the battery.
[0141] Compared with Examples 1-2, the electrochemical performance of Comparative Example 3 is poor because the reduction temperature is reduced to 450°C in Comparative Example 3. The lower temperature leads to incomplete reduction reaction of tin oxide, and the generated tin nanoparticles may contain some unreduced oxidized substances. This not only reduces the effective content of tin nanoparticles, but also affects their catalytic activity. Due to insufficient reduction, the crystallinity of tin nanoparticles is poor, the particle size distribution is uneven, and the dispersibility on the graphite substrate is also affected. In the subsequent silicon deposition process, the uneven tin nanoparticles cannot provide a uniform catalytic environment for silicon atoms, resulting in uneven growth of silicon nanowires. There may be some areas where silicon nanowires grow sparsely and have small diameters, while in other areas, due to high local catalytic activity, silicon nanowires grow excessively and have large diameters. This uneven silicon nanowire structure will cause a series of problems during the charge and discharge process of lithium-ion batteries. At the same time, the uneven structure is more susceptible to stress during the cycle, resulting in the breakage and pulverization of silicon nanowires, thereby deteriorating the cycle stability of the battery and accelerating capacity decay.
[0142] Compared with Examples 1-2, the electrochemical performance of Comparative Example 4 is poor. This is because in Comparative Example 4, the silicon deposition temperature is increased to 750°C. Excessively high temperatures greatly increase the deposition rate of silicon atoms, causing the silicon nanowires to grow too fast, leading to a series of problems. First, the diameter of the silicon nanowires will increase significantly and become uneven, and some areas may form thick silicon nanowires due to excessive growth; secondly, the rapidly growing silicon nanowires are prone to entanglement and agglomeration with each other, destroying the originally ordered structure, making it difficult for the material to evenly withstand the volume changes caused by the insertion and extraction of lithium ions during the charge and discharge process, thereby causing stress concentration and accelerating the pulverization and structural damage of the material. In lithium-ion battery applications, these problems will significantly reduce the cycle stability of the battery.
[0143] Compared with Examples 1-2, the electrochemical performance of Comparative Example 5 is poor because the oxidation time is shortened to 0.5h in Comparative Example 5. Such a short oxidation time causes the stannous chloride dihydrate to be unable to be completely oxidized, and a large amount of unoxidized or incompletely oxidized intermediates may be produced. In the subsequent reduction process, these incompletely oxidized substances will affect the formation of tin nanoparticles. On the one hand, the number of tin nanoparticles may decrease because there are not enough oxidation products to provide sufficient tin sources; on the other hand, its particle size distribution will become uneven, and some areas may form larger or smaller particles due to differences in local oxidation degree. In the silicon deposition stage, uneven tin nanoparticles will cause uneven growth of silicon nanowires. In some areas, due to the lack of sufficient catalytic sites, the silicon nanowires grow sparsely, while in other areas, due to excessive local catalytic activity, silicon nanowires that grow too fast and have too thick diameters may appear. This uneven structure will hinder the transmission of lithium ions and the conduction of electrons during the charge and discharge process of lithium-ion batteries. At the same time, the uneven structure is more susceptible to stress during the cycle, making the silicon nanowires easy to break and pulverize, thereby seriously affecting the cycle stability of the battery.
[0144] Compared with Examples 1-2, the electrochemical performance of Comparative Example 6 is poor, because the reduction time of Comparative Example 6 is shortened to 1h. Such a short reduction time makes it impossible for the reduction reaction of tin oxide to proceed fully. On the one hand, a large amount of tin oxide will fail to be completely converted into tin nanoparticles, resulting in a reduction in the actual amount of tin nanoparticles generated, reducing the number of catalytic active sites. On the other hand, due to insufficient reduction, the generated tin nanoparticles have poor crystallinity, uneven particle size distribution, and unsatisfactory dispersibility on the graphite substrate. In the subsequent silicon deposition stage, these defects seriously hinder the growth of silicon nanowires. It is difficult for silicon atoms to stably deposit on uneven and insufficiently active catalytic sites, resulting in sparse growth of silicon nanowires, uneven diameters, and some areas may not even grow normally. When applied to lithium-ion batteries, this undesirable structure will greatly affect battery performance. At the same time, during the battery cycle, the uneven silicon nanowire structure is more likely to produce stress concentration due to volume changes, which in turn causes the silicon nanowires to break and pulverize, seriously weakening the cycle stability of the battery.
[0145] Compared with Examples 1-2, the electrochemical performance of Comparative Example 7 is poor. This is because the dispersion of tin dioxide on the graphite surface is not ideal, and the subsequent reduction process remains in a large size or agglomerated state. During the silicon deposition process, the uneven tin nanoparticles cannot provide sufficient and uniform catalytic sites for silicon atoms, resulting in uneven growth of silicon nanowires. When used in lithium-ion batteries, this uneven structure will hinder the transmission of lithium ions and the conduction of electrons. At the same time, the uneven structure is more susceptible to stress during the cycle, making the silicon nanowires easy to break and pulverize, thereby seriously affecting the cycle stability of the battery.
[0146] Compared with Examples 1-2, the electrochemical performance of Comparative Example 8 is poor. This is because the dispersion effect of anhydrous stannous chloride on the graphite surface is not ideal, and the subsequent reduction process remains in a large size or agglomerated state. During the silicon deposition process, the uneven tin nanoparticles cannot provide sufficient and uniform catalytic sites for silicon atoms, resulting in uneven growth of silicon nanowires. When used in lithium-ion batteries, this uneven structure will hinder the transmission of lithium ions and the conduction of electrons. At the same time, the uneven structure is more susceptible to stress during the cycle, making the silicon nanowires easy to break and pulverize, thereby seriously affecting the cycle stability of the battery.
Claims
1. A catalyst, characterized in that It contains tin nanoparticles; the particle size of the tin nanoparticles is 20-120nm; the catalyst is attached to the surface of the catalyst carrier; the particle size of the catalyst carrier is 1-100μm; the catalyst carrier is selected from at least one of carbon-based materials, ITO-based materials and carbonaceous polymers; Preferably, the particle size of the tin nanoparticles is 46 nm or 70 nm; Preferably, the particle size of the catalyst carrier is 4-28 μm; Preferably, the D50 of the catalyst carrier is 8-15 μm, for example 12.3 μm; Preferably, the catalyst carrier is a carbon-based material and / or a carbonaceous polymer, such as graphite; more preferably, the graphite is one or more of natural graphite, artificial graphite and expanded graphite; wherein the D 50 Preferably, it is 8 to 15 μm, for example, 12.3 μm; Preferably, when the catalyst carrier is a carbon substrate, the size of the carbon substrate is 4-28 μm, and the BET area is 1-150 m 2 / g; Preferably, the mass ratio of catalyst to catalyst carrier is (0.05-0.3):
1.
2. A method for preparing a catalyst, characterized in that: The method comprises the following steps: oxidizing and reducing a mixture of a catalyst carrier, stannous chloride dihydrate and a solvent to obtain tin nanoparticles attached to the catalyst carrier; the oxidation temperature is 180-500° C.; the oxidation time is 1-2 hours; the reduction temperature is 500-900° C.; the reduction time is 2-4 hours; the particle size of the catalyst carrier is 1-100 μm; the catalyst carrier is selected from at least one of a carbon-based material, an ITO-based material and a carbonaceous polymer; Preferably, the steps satisfy one or more of the following conditions: a. The solvent is one or more of methanol, ethanol, isopropanol and deionized water, for example, a mixture of deionized water and ethanol in a volume ratio of 7:3; b. The mass ratio of the catalyst support, stannous chloride dihydrate and the solvent is 1:(0.05-0.3):(2-5), for example 1:0.06:2.5 or 1:0.2:2.5; c. Before the oxidation, the step of: removing the solvent and then drying; preferably, the solvent removal method is spray drying, impregnation, sol-gel or co-precipitation; the drying time is 6-24h, for example, 12h; the drying temperature is 90-200°C, for example, 120°C; c. The oxidation atmosphere is air or oxygen atmosphere; the oxidation temperature is 220-450°C, for example, 350°C or 400°C; and / or, the oxidation time is 1-2h, for example, 1h or 2h; and / or, the oxidation heating rate is 5-15°C / min, for example, 10°C / min; d. The reduction is carried out using a reducing gas, which is H2 or CO; and / or, the reducing gas is also mixed with a non-reactive gas when used, and the non-reactive gas is preferably nitrogen or argon; the volume ratio of the reducing gas to the non-reactive gas is (1-10):(90-98), for example, 5:95; and / or, the flow rate of the reducing gas is 2-6L / min, for example, 4L / min; and / or, the reduction temperature is 600-800°C, for example, 600°C or 700°C; and / or, the reduction time is 2h; and / or, the reduction heating rate is 2-10°C / min, for example, 5°C / min; e. The mixture is obtained by wet mixing; the wet mixing preferably comprises the following steps: Firstly dissolving the stannous chloride dihydrate, and then adding the catalyst carrier; f. The particle size of the catalyst carrier is 4-28 μm; g. The D50 of the catalyst support is 8-15 μm, for example 12.3 μm; h. The catalyst carrier is a carbon-based material and / or a carbonaceous polymer, such as graphite; more preferably, the graphite is one or more of natural graphite, artificial graphite and expanded graphite; wherein the D50 of the graphite is preferably 8-15 μm, such as 12.3 μm; wherein, when the catalyst carrier is a carbon substrate, the size of the carbon substrate is 4-28 μm, and the BET area is 1 to 150 m 2 / g, for example 1.524m 2 / g.
3. A catalyst, characterized in that The catalyst is prepared by the method for preparing the catalyst according to claim 2.
4. A silicon-tin composite material, characterized in that: It comprises a catalyst carrier, a catalyst and a silicon nanowire that grows outward with tin nanoparticles as anchor points; the catalyst is the catalyst as claimed in claim 1 or 3; the catalyst carrier is the catalyst carrier as claimed in claim 1 or 3; the content of the silicon nanowire is 24-80%, the percentage is the mass percentage of silicon in the total amount of silicon and tin; the diameter of the silicon nanowire is 20-100nm, and the length of the silicon nanowire is 0.1-10μm; the tin content of the silicon-tin composite material is 20-76%, the percentage is the mass percentage of tin in the total amount of silicon and tin; preferably, the diameter of the silicon nanowire is 35nm or 27nm; Preferably, the length of the silicon nanowire is 5.2 μm or 2.5 μm; Preferably, the content of the silicon nanowires is 73% or 58%; Preferably, the silicon content of the silicon-tin composite material is 73% or 58%; Preferably, the tin content of the silicon-tin composite material is 27% or 42%.
5. A method for preparing a silicon-tin composite material, characterized in that: It includes the following steps: Mixing the catalyst according to claim 1 or 3 with a silicon source under heating conditions; the heating temperature is 400-700° C.; Preferably, the silicon source is one or more of disilane, chlorosilane, dichlorosilane, trichlorosilane, phenylsilane, diphenylsilane and trisilane; Preferably, the heating rate is 2-10°C / min, for example 5°C / min; Preferably, the heating temperature is 450-550°C, such as 550°C or 450°C; Preferably, the heating time is 30-200 min, for example, 60 min; Preferably, the flow rate of the silicon source is 2-6 L / min, for example 5 L / min.
6. A silicon-tin composite material, characterized in that: The silicon-tin composite material is prepared by the preparation method of the silicon-tin composite material according to claim 5.
7. A carbon-coated silicon-tin composite material, characterized in that: It comprises a silicon-tin composite material and a carbon coating layer on the outside of silicon nanowires; the silicon-tin composite material is the silicon-tin composite material as claimed in claim 4 or 6; the particle size of the carbon-coated silicon-tin composite material is 1-50 μm; the silicon content of the carbon-coated silicon-tin composite material is 0.96-70%, the percentage is the mass percentage of silicon in the total amount of silicon, tin and carbon, the tin content of the carbon-coated silicon-tin composite material is 0.96-30%, the percentage is the mass percentage of tin in the total amount of silicon, tin and carbon, and the thickness of the carbon coating layer is 10-100 nm; Preferably, the tin content of the carbon-coated silicon-tin composite material is 2.70% or 8.06%; Preferably, the silicon content of the carbon-coated silicon-tin composite material is 7.21% or 11.29%; Preferably, the carbon content of the carbon-coated silicon-tin composite material is 1-95%, such as 90.09%, 80.65% or 1.96%; Preferably, the thickness of the carbon coating layer of the carbon-coated silicon-tin composite material is 12 nm or 55 nm.
8. A method for preparing a carbon-coated silicon-tin composite material, characterized in that: It includes the following steps: The mixture of the silicon-tin composite material and the carbon source according to claim 6 is heated; Preferably, the carbon source is one or more of ethanol, benzene, methane, propane and acetylene; Preferably, the flow rate of the carbon source is 2-6 L / min, for example 4 L / min; Preferably, the heating temperature is 500-800°C, preferably 600-700°C; Preferably, the heating time is 0.3-3h; Preferably, the heating rate is 2-10°C / min, such as 5°C / min.
9. Use of the silicon-tin composite material according to claim 4 or 6, or the carbon-coated silicon-tin composite material according to claim 7 in a negative electrode of a lithium-ion battery.
10. A battery, characterized in that: It comprises the silicon-tin composite material according to claim 4 or 6 and the carbon-coated silicon-tin composite material according to claim 7.
Citation Information
Patent Citations
Method for preparing Si multi-nanowire array by using tin dioxide
CN106637127A
Method for preparing material comprising silicon nanowires and tin
CN117545716A